2 - Circus Ethiopia: Dilemmas of a Development- oriented Entertainment NGO in Ethiopia - Getachew, Aklil (Africa Development, 2021)
As in most other sub-Saharan African countries, the circus had no historical precedents in Ethiopia until it was introduced as a foreign art form by a Westerner in the early 1990s, recruiting children as its performers. ‘Circus Ethiopia’ gradually became adapted to and invested with ‘Ethiopian culture’. While initially conceived as a circus proper, focusing primarily on circus art and the development of circus performance as an art or cultural form in Ethiopia, it later became an NGO that also tried to engender social or community development. Accordingly, Circus Ethiopia assumed two responsibilities: an artistic (self-defined) and a civic (donor-defined) responsibility, and still functions both as an artistic medium and as an NGO by using circus arts to educate and inform its audiences on various social and health-related issues. The paper examines to what extent Circus Ethiopia has been able to maintain itself in the light of this double, possibly contradictory, mission, and in view of its institutional dependence on outside sources. In doing so, it identifies the potential of the circus, as a cultural activity, to play an important role in development work. Furthermore, it uncovers some problems Circus Ethiopia – bein a Southern NGO – faces and deals with regarding its sustainability.